Peran Pendidikan Agama Islam Terhadap Tradisi Pingitan Pernikahan Di Desa Pangkalan Batang Bengkalis - Sugiarto, Wira; Larasaty, Esty; Rohmah, Sofiyana (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2023)
The purpose of this study was to determine the role of islamic religious education in the Javanese Traditional Wedding Bride Pingitan tradition. As for this study using qualitative methods, by taking a normative approach. This research can also be categorized as field research, and is a continuation of descriptive research that aims not only to describe certain characteristics. But also analyze and explain why or how it happened. The data criteria obtained are primary and secondary data. Data collection techniques used are observation, interviews, documentation, and literature study. From the results of the research that the author did, the pre-wedding traditional wedding bride pingitan is, women or prospective brides are prohibited from traveling, leaving, the house or meeting future husbands from the specified time until the marriage contract takes place in order to avoid distress. This tradition and some people consider it irrelevant to apply it today. This tradition basically does not conflict with islamic law because it is in accordance with what has been prescribed by islam in practice.